3D printing silk-gelatin-propanediol scaffold with enhanced osteogenesis properties through p-Smad1/5/8 activated Runx2 pathway. Issue 12 (17th August 2021) - Liu, Caiyun; Bai, Zhenzu; Lin, Jiayu; Jiang, Kai; Huang, Shan; Zheng, Weijia; Chen, Ruifen; Xiang, Yang; Wang, Xiaoyan; Liu, Long
Abstract: The application of 3 D printing technology in tissue engineering has become increasingly important. However, due to the limitations of bio-ink, there are still some remaining problems. For example, the major challenge for ideal bio-ink is to maintain stable 3 D structure and good biocompatibility in the meantime while conventional gels are week and nearly unprintable. So, the development of new bio-ink material with improved rheological and mechanical properties is highly demanded to avoid compromising biocompatibility for tissue engineering. Silk fibroin (SF), a natural degradable polymer, is considered to be a proper material for the preparation of bio-inks. We used SF, gelatin, and polyols as raw materials to fabricate bio-inks and scaffolds. We evaluated the rheological properties and printability of bio-inks with a rotational rheometer and a 3 D printer. The scaffolds were prepared by crosslinking and freeze-drying technologies. The biocompatibility and osteoinductive functions of scaffolds were investigated by evaluating proliferation, osteogenic differentiation and related cell signaling of cultured MC3T3-E1 cells. The results showed that the scaffolds using SF, Gel and propanediol (PG) not only had good rheological properties and storage modulus, but also could better enhance osteogenic specific genes expression mediated by Smad1/5/8 and Runx2 pathways. What is more, morphological characterization showed that α-mem incubation could help scaffold form porous structure on its surface, which could shed a light on a new 3 D bio-printed bone repair scaffold with both naturally emerged and CAD-designed porous structure. Our findings provide a potential biomaterial for the treatment of bone tissue regeneration.